Ana Akım İktisat ve Kapitalizm İlişkisi: Eleştirel Bir Giriş - Levent, Adem (Muş Alparslan Üniversitesi, 2020)
Political economy, which stands out as the general science of modernity, has a wide field of study such as institutions, class, law, polity and economy without being subject to any disciplinary limitations. As political economy developed during the periods of commercial and industrial capitalism, it sought to analyze the social reality that had developed itself as a whole totality. However, in the late 19.th century, political economy narrowed the research object as it turned into economics within the context of the intellectual division of labour between social sciences and the concept of utility value to solve the pricing problem. As a result, economics, by excluding capitalism from being an object of research, accepts the technical issues such as market balance, consumer benefit, and individual profit maximization as the fundamental research object and continues its scientific activities. Therefore, in this paper, it is claimed that today’s economics could not analyze the capitalist system which directly affects our daily life as it progresses in a technical dimension.

Modernliğin genel bilimi olarak öne çıkan politik iktisat, herhangi bir disipliner sınırlamaya tabi olmadan kurumlar, sınıf, hukuk, politika ve ekonomi gibi geniş bir inceleme alanına sahiptir. Politik iktisat, ticari ve sanayi kapitalizmi dönemlerinde geliştiği için kendini var eden toplumsal gerçekliği bir bütün olarak analiz etmeye çabalamıştır. Ancak 19. yüzyılın sonlarında fiyatlama sorununu çözmek için fayda değer kavramının öne çıkması ve sosyal bilimler arasında gerçekleşen entelektüel işbölümü kapsamında politik iktisat, iktisada dönüşürken araştırma nesnesini daraltmıştır. Bunun sonucu iktisat bilimi, kapitalizmi araştırma nesnesi olmaktan çıkararak piyasa dengesi, tüketici faydası, bireysel kâr maksimizasyonu gibi disiplin içi teknik meseleleri temel araştırma nesnesi olarak kabul edip bilimsel faaliyetlerine devam etmektedir. Bu nedenle bu çalışmada günümüz iktisat biliminin, teknik bir boyutta ilerlediği için gündelik yaşamımızı doğrudan etkileyen kapitalist sistemi analiz edemediği iddia edilmektedir.
The Relationship between Mainstream Economics and Capitalism: a Critical Introduction
anemon
Keywords: Mainstream Economics; Economic Sociology; Political Philosophy; Social Theory; Capitalism; İktisat Bilimi; İktisat Sosyolojisi; Politik Felsefe; Sosyal Teori; Kapitalizm